Percepção visual da forma em humanos: a utilização de quadros de Dali na marcação da esquizofrenia - Nogueira, Renata Maria Toscano Barreto Lyra (2006)
Schizophrenia, one of the main forms of psychotic upheaval, can be folloied of damage in the representation and visuo-spatial perception. The aim of the work was to investigate alterations in the visual perception in patients with of schizophrenia, using some pictures of surrealista painter Salvador Dalí. Sixty adults participated in the experiments, thirty without neuropsiquiátrica pathology (Control Group -GC) and thirty with schizophrenia in remissive phase (Experimental Group - GE). The participants of the GC and GE presented equivalents degree of escolaridade (M= 11,6, DP= 4,78 e M= 8,26, DP= 2,91; GC e GE, respectivelly) and etárias bands ((M= 28,3, DP= 5,35 e M= 31,23, DP= 6,78; GC e GE, respectivelly). All volunteers had good visual acuity. Twenty and four pictures of Salvador painter from there photographed in 20 dimension x 30 cm, based on categories previously established had been used. The photographs of the pictures had been presented the volunteers successively, after to another one without limit of time for comment. After the presentation of each photograph, the participant indicated the figure that more was distinguished. After that, each engraving was measured in centimeter and used to calculate the visual angle for the mathematical function tang alpha-1. The data had been collected in the Centers of Atenção Psicossocial (CAPS) of the cities of João Pessoa - PB and Recife - PE. The results had shown significant difference between the two groups (F 1, 58 = 550, 62, p<0,001). That is, the majority of the participants of GE preferred figures with average size bigger (between 10-15°) of that the GC that preferred figures with lesser average size (4-5°). In the generality, the figures indicated for GE had been in average 3 times bigger than the indicated ones for the GC. These data had indicated that the schizophrenia carriers had from there presented alteration in the visual perception of pictures of Salvador and that the same ones can be used to mark and to study this pathology.